1980
DOI: 10.2307/1240203
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Regional Conjunctive Water Management

Abstract: An optimal control model is used to determine the socially optimal spatial and temporal allocation of groundwater and surface water among agricultural and urban uses. The control model is described briefly and its advantages over other dynamic models are enumerated. Optimal rates of groundwater pumpage over the planning horizon were highly sensitive to increasing energy costs. Groundwater basins are shown to react differently to alternative economic and hydrological parameters. In a dynamic setting, a policy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 12 publications
1
34
0
3
Order By: Relevance
“…3). This falls between the low estimates obtained in several studies (e.g., 0.01% in Gisser and Sanchez 1980;Gisser 1983;Allen and Gisser 1984;0.28% in Nieswiadomy 1985;0.3% in Dixon, 1989; 2.6% in Knapp and Olson 1995; 2.2% in Burness and Brill 2001;and 4% in Provencher and Burt 1994), and high estimates in others (e.g., 10% in Noel, Gardner, Moore 1980;14% in Feinerman and Knapp 1983;17% in Brill and Burness 1994). While a detailed analysis of the reasons for the size of the gains is beyond the scope of this article, it is worth noting that the recharge to storativity ratio and the demand slope to storativity ratio in Honolulu are small compared with those in Gisser and Sanchez (1980).…”
Section: Efficient Managementsupporting
confidence: 44%
See 1 more Smart Citation
“…3). This falls between the low estimates obtained in several studies (e.g., 0.01% in Gisser and Sanchez 1980;Gisser 1983;Allen and Gisser 1984;0.28% in Nieswiadomy 1985;0.3% in Dixon, 1989; 2.6% in Knapp and Olson 1995; 2.2% in Burness and Brill 2001;and 4% in Provencher and Burt 1994), and high estimates in others (e.g., 10% in Noel, Gardner, Moore 1980;14% in Feinerman and Knapp 1983;17% in Brill and Burness 1994). While a detailed analysis of the reasons for the size of the gains is beyond the scope of this article, it is worth noting that the recharge to storativity ratio and the demand slope to storativity ratio in Honolulu are small compared with those in Gisser and Sanchez (1980).…”
Section: Efficient Managementsupporting
confidence: 44%
“…There are other excellent models in the literature with spatial and temporal components (e.g., Provencher 1993;Provencher and Burt 1994;Zeitouni and Dinar 1997;Reinelt 2005;Taghavi, Howitt, and Marino 1994;Dinar and Xepapadeas 1998;Noel, Gardner, and Moore 1980;Noel and Howitt 1982). However, they usually either add transport costs in the numerical simulations, after the analytical model has already been articulated, or their optimization objectives are different from ours, e.g., some minimize cost rather than maximize welfare; some use an exogenous water price; and some do not attempt to provide analytical results such as our equation (10).…”
Section: The Modelmentioning
confidence: 99%
“…Noel et al (1980) found that control increases the value of groundwater in the Yolo basin in California by 10%. Lee et al (1981) found that control raised the net benefit of groundwater in the Ogallala basin by only 0.3%.…”
Section: Testing the Robustness Of Gsementioning
confidence: 99%
“…This dual use of groundwater and surface water is known as conjunctive water management. Both the economic and institutional aspects of conjunctive water management are well studied [1][2][3], but the influence of irrigation management on the non-market benefits of multiple ecosystem services (in particular, groundwater supply, surface water purification, and greenhouse gas (GHG) reduction) has received less attention. The choice to use conjunctive water management changes the aquifer volume, which in turn affects the crops grown, and the crop production decisions influence nutrient and sediment runoff and GHG emissions.…”
Section: Introductionmentioning
confidence: 99%